Interactive Media: The Semiotics of Embodied Interaction - O'Neill, Shaleph; SpringerLink (Online service) (London : Springer London, 2008)
Interactive media is pervasive. The colonization of our everyday lives by the computational power of the silicon chip is a fundamental feature of our digital age, and raises important questions such as: What does this mean for us as inhabitants of such media rich environments? How can we make sense of these media and the ways in which they have changed our interactions? What theories can we draw on to help us make sense of life in the digital age? Human Computer Interaction has been looking at versions of these questions for a long time now, but as technology advances so quickly it is hard to keep pace with the changes. In reflecting on some of these issues and by providing a way to relate some of the disparate threads of theory from fields such as phenomenology, cognitive science, semiotics and the ecological theory of perception, Shaleph O$1 (BNeill provides an exploration of the theories that impact our understanding over a spectrum of interactive media. Dr. Shaleph O$1 (BNeill is Course Director of Interactive Media Design at the University of Dundee.s
Media, Mediation and Interactive Media -- Approaching Interaction -- Affordance: A Case of Confusion -- Semiotic Theory -- Semiotics and Screen Based Interaction -- Semiotics and Interactive Environments -- Being-with-Media -- Embodied Semiotics -- Understanding Interactive Media -- Concluding Thoughts.
Keywords: Computer science; Multimedia information systems; User interfaces (Computer systems).; Multimedia systems; Computer Science; User Interfaces and Human Computer Interaction; Multimedia Information Systems; Media Design; Electronic books